China: a stabilizing or deflationary influence in East Asia?The problem of conflicted virtue - Gunther Schnabl (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2003)
Rapidly growing Chinese exports are middle-tech - and increasingly high-tech - manufactured goods. China runs a huge and growing bilateral trade surplus with the United States, and the position of Japan has changed radically from being a net exporter to China in the 1980s and most of 1990s to being a net importer today. China's smaller East Asian industrial competitors such as Taiwan, Korea, and Singapore face fairly difficult readjustment problems. However, China is a huge importer of primary products and industrial raw materials and runs large import surpluses with the ASEAN group. On the macroeconomic side, China has been a stabilizing influence. While maintaining steady high growth and exchange rate stability at 8.3 yuan per dollar since 1994, it has largely avoided, and thus dampened, the business cycles of its East Asian trading partners. But there are potential clouds on this horizon. Since 1995, China has run with moderate multilateral trade surpluses coupled with large inflows of foreign direct investment. The resulting balance of payments surpluses have led to a rapid buildup of liquid dollar claims on foreigners - both in official exchange reserves and, less obviously, in stocks held privately or in China's nonstate sectors. This increasing private dollar overhang leads to what we call the syndrome of conflicted virtue. If there is no threat that the renminbi will appreciate, private portfolio equilibrium for accumulating and holding both dollar and renminbi assets can be sustained. However, foreigners, particularly Japanese, are upset with China's excessive mercantile competitiveness. They are urging China's government to appreciate the renminbi - and show greater future exchange rate flexibility, which could lead to repetitive appreciations. The result would be severe deflation throughout China's economy and a zero-interest liquidity trap - as in Japan, when forced into repeated appreciations of the yen in the 1980s into the mid 1990s.
urn:nbn:de:bsz:21-opus-18661
Keywords: F15; F31; F33; 330